Leadership behavior and organizational climate in Widya Mandala Catholic University in Surabaya-Indonesia - Prasetyo, Vincent Winarto (Animo Repository, 1980)
This study investigates the relationship between the administrators' leadership behavior and the organizational climate in Widya Mandala Catholic University in Surabaya, Indonesia. This study made use of a combination of descriptive and analytical methods of research, using the questionnaires as the principal instrument, the Leader Behavior Description Questionnaire (LBDQ) and the Organizational Climate Description Questionnaire (OCDQ). The subjects of the study consisted of two population frames, namely: the administrators and the teachers of Widya Mandala Catholic University during the school year 1979-1980. The data gathered from the respondents were subjected to a statistical treatment which included tallying, computation of average ratings, percentage, ranking, Pearson-r coefficient correlation and the use of t-test and ANOVA to determine the significant differences. The conclusions of the study are: 1. Generally, the age characteristics of the administrators clustered around a mean point estimate of 41.33 years and the age of the teachers clustered around a mean point average of 35.81 years. The length of service of the administrators clustered around a mean point estimate of 7 years and the teachers' clustered around a mean point estimate of 5.44 years. 2. Both the administrators and teachers had the same high perception of administrators' leadership behavior in the dimensions of consideration and initiating structure. 3. The way the administrators and the teachers perceived the organizational climate was basically the same. 4. There were significant relationships between the dimensions of leadership behavior and Disengagement, Esprit, Aloofness, Production Emphasis, Thrust and Consideration of the organizational climate dimensions. However, no significant relationship existed between the dimensions of leadership behavior and Hindrance and Intimacy of the organizational climate dimensions. 5. Generally, in the selected variables as sex, age, educational qualification, and length of service, the administra